2013 12th IEEE International Conference on Trust, Security and Privacy in Computing and Communications 2013
DOI: 10.1109/trustcom.2013.178
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Aware Task Scheduling Algorithm for a Heterogeneous Data Center

Abstract: In recent years, rapidly increasing Internet-scale services are deployed in production data centers, which causes a huge amount of energy consumption and environment problem. It is a challenge for these data centers to reduce energy consumption while satisfying the increasing performance requirement of these services. Servers in data centers are usually heterogeneous, which makes task scheduling process more sophisticated. This paper first analyzes and explores two types of heterogeneity from a publicly Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Such requests are inherently multi-dimensional and simultaneously ask for multiple resources such as processor cycles, network bandwidth, and storage space [23], [27], [34] (see also multi-dimensional load balancing in virtualization [28], [32]). In addition to the multi-dimensionality of resource requests, another challenge is the heterogeneity of server clusters because of incremental hardware deployment and the use of dedicated specialized hardware for particular tasks [1], [24], [45]. As a third source of non-uniformity, the objective of the load balancing exercise is often defined by the application at hand and the resource being allocated.…”
Section: Introductionmentioning
confidence: 99%
“…Such requests are inherently multi-dimensional and simultaneously ask for multiple resources such as processor cycles, network bandwidth, and storage space [23], [27], [34] (see also multi-dimensional load balancing in virtualization [28], [32]). In addition to the multi-dimensionality of resource requests, another challenge is the heterogeneity of server clusters because of incremental hardware deployment and the use of dedicated specialized hardware for particular tasks [1], [24], [45]. As a third source of non-uniformity, the objective of the load balancing exercise is often defined by the application at hand and the resource being allocated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are a series of research works to study the task scheduling problem in CPCSs, an energyaware task scheduling algorithm based on the greedy algorithm is proposed for the heterogeneous cloud in [16]. To realize the implementation of scientific workflows, a novel energy-efficient resource allocation scheme was proposed in response to the expanding cloud [17].…”
Section: Related Workmentioning
confidence: 99%
“…In general, the most intensive phase in EnReal was the resource monitoring that takes quadratic time complexity. Furthermore, the performance evaluation results showed that EnReal outperformed the modi ed energy-aware Greedy-D (Zhang et al 2013) algorithm in terms of energy e ciency by 18% in average.…”
Section: Energy Aware Scheduling For Multiple Workflowsmentioning
confidence: 99%